E-Homestay Application Based on Decision Support System for Optimizing Tourism - Febriansyah; Siti Muntari (Politeknik Ganesha Medan, 2024)
Pagar Alam City, a growing tourist destination, has seen a steady increase in visitors each year, driving greater demand for accommodations, especially homestays. Homestays are often favored by tourists due to their affordability compared to hotels. However, many tourists face challenges in selecting a suitable homestay that meets their preferences and needs. To address this issue, this study proposes the development of a web-based Decision Support System (DSS) integrated into the e-homestay platform. The system utilizes the Simple Additive Weighting (SAW) method, chosen for its capability to assess multiple alternatives based on specific weighted criteria, including price, facilities, location, distance, and guest ratings. This approach is designed to assist tourists in identifying the optimal homestay that aligns with their preferences and budget, thereby enhancing their overall travel experience in Pagar Alam City. Moreover, the platform has the potential to promote local economic growth by supporting digital marketing of homestays, while also contributing to sustainable tourism development and management.